Revisiting the surgical table: An analysis of surgical dose-response in Asian exotropia - I-Wen Lai; Li-Li Wu; Yao-Lin Liu; Tzu-Hsun Tsai (Journal of the Formosan Medical Association)
Background: Previous research on the factors associated with surgical dose-response in strabismus surgery for exotropia has yielded inconsistent results. This study determined the factors influencing surgical dose-response in exotropia patients who underwent recession and resection (R&R). Methods: Exotropia patients who underwent unilateral R&R at the National Taiwan University Hospital between 2006 and 2021 were evaluated. Deviation-angle differences in prism diopters (PD) were measured preoperatively and at 1 month postoperatively. Surgical dose-response (PD/mm) was defined as the difference in deviation angle (in PD) divided by the surgical dose in millimeters. Linear and non-linear regression models were used to evaluate the influence of variables including age, sex, axial length, and preoperative deviation on surgical dose-response. Results: Overall, 295 patients (162 children; 133 adults) were included. Average surgical dose-response in the pediatric and adult groups was 2.82 ± 0.60 PD/mm and 3.02 ± 0.62 PD/mm, respectively. Male sex was negatively correlated with surgical dose-response in children. The surgical dose-response was larger in adults with longer axial length (>25.64 mm) and patients with larger preoperative deviation (>42.6 PD and >38.7 PD in pediatric and adult groups, respectively). Surgical dose-responses peaked at 35.1 years. Conclusion: Age, axial length, and preoperative deviation have a nonlinear effect on surgical dose-responses in exotropia patients undergoing R&R. Surgical dose-responses were larger in patients in young adulthood, with longer axial length and larger preoperative deviation angle. A table with fitted values for surgical dose-response based on age, axial length, and preoperative deviation was established for clinical reference.